MENEGASKAN SUPREMASI KRISTUS DALAM DINAMIKA PEMBERITAAN INJIL DI KONTEKS INDONESIA - Raqia Bat Manukrante; Iramayanti Pasangla', Febrianti Panjaitan, Betria Putri Rahayu Mbahas, Geovanni Prima Putra Pas (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This article aims to examine theologically and practically the meaning and implications of Christ's supremacy in the context of evangelism in Indonesia. Christ's supremacy is understood as Christ's absolute sovereignty over all creation, both cosmically, soteriologically, and ecclesiastically, as affirmed in New Testament texts such as Colossians 1:15-20 and Ephesians 1:22. Using a qualitative approach and a literature review method, this article examines the relationship between Christ's supremacy and the socio-religious dynamics of pluralistic Indonesia. Challenges such as intolerance, cultural resistance, and secularism form an important backdrop for considering evangelism strategies. One of the article's main findings is the importance of contextualization as an effort to present Christ relevantly in local cultures without losing the authority of the Gospel. Christ's supremacy is not only a doctrinal foundation but also a strategic direction in the church's mission. Therefore, the church is required to develop a dialogical, inclusive, and transformative evangelism approach that not only conveys the message of salvation but also presents Christ in concrete service to society. This overall study shows that the supremacy of Christ is a solid spiritual and missiological foundation for the Indonesian church in facing the challenges of the times and remaining faithful to the call to evangelism